1981
DOI: 10.1080/0097840x.1981.9936831
|View full text |Cite
|
Sign up to set email alerts
|

Moderator Variables in Life Stress and Illness Relationship

Abstract: The relationship between life stress and physical illness was examined for the effects of potential moderator variables: The Sensation-Seeking Scale, health Locus of Control Scale, and Myers-Briggs Type Indicator. The Sensation-Seeking Scale proved to be a moderator with high sensation seekers (highest quartile) showing no significant correlations between life change and illness, while low sensation seekers (lowest quartile) showed a significant correlation. The Health Locus of Control Scale failed to differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Rahe (1979) suggested that the presence of personal-modifying factors might reduce negative responses to stress induced by life change. Researchers have isolated such modifying factors as social sup-port, coping abilities, physical vigor, and locus of control (Jenkins, 1979;Lloyd, 1980;Cooley & Keesey, 1981). Lloyd (1980) pointed out the need for further research to investigate the relationship between life-change scores and indices of depression, as well as to identify factors that mediate this relationship.…”
mentioning
confidence: 99%
“…Rahe (1979) suggested that the presence of personal-modifying factors might reduce negative responses to stress induced by life change. Researchers have isolated such modifying factors as social sup-port, coping abilities, physical vigor, and locus of control (Jenkins, 1979;Lloyd, 1980;Cooley & Keesey, 1981). Lloyd (1980) pointed out the need for further research to investigate the relationship between life-change scores and indices of depression, as well as to identify factors that mediate this relationship.…”
mentioning
confidence: 99%
“…Social support may be one of the most important of these. Other researchers have found links between social variables, illness, and birth complications (22)(23)(24). Other researchers have found links between social variables, illness, and birth complications (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…For example, when feeling upset, depressed, or anxious, people may see their health as poor, their life as unsatisfactory, 34,35 and themselves as less confident. It is also feasible that these are, to some extent, personality traits 36–38 . Their origin may date back to childhood experience, as well as to the present mental state.…”
Section: Introductionmentioning
confidence: 99%
“…It is also feasible that these are, to some extent, personality traits. [36][37][38] Their origin may date back to childhood experience, as well as to the present mental state. Thus, the second aim of the present study was to investigate correlates of each of these concepts in terms of: (i) present mental state, (ii) personality, and (iii) childhood experiences.…”
Section: Introductionmentioning
confidence: 99%